FERONIA interacts with NPL4 to regulate immunity gene mRNA nucleocytoplasmic transport in response to plant immunity - Guan, Li (Plant science : an international journal of experimental plant biology, 2025)
Copyright © 2025 Elsevier B.V. All rights reserved.